Neutrophil extracellular traps mediate the crosstalk between plaque microenvironment and unstable carotid plaque formation - Yu Cao; Minghui Chen; Xinyu Jiao; Shuijie Li; Dong Wang; Yongxuan Zhan; Jiaju Li; Zhongfei Hao; Qingbin Li; Yang Liu; Yan Feng; Ruiyan Li; et al. (Experimental and Molecular Medicine)
Abstract The development of unstable carotid atherosclerotic plaques is associated with the induction of neutrophil extracellular traps (NETs) via the activation of diverse inflammatory mediators in the circulating bloodstream. However, the underlying mechanisms through which NETs influence the microenvironment of atherosclerotic plaques and contribute to the development of unstable carotid plaques remain largely elusive. The objective of this study was to elucidate the role of myeloid differentiation protein 1 (MD-1, LY86)-induced NETs underlying the crosstalk between unstable plaque formation and the plaque microenvironment. We employed bioinformatics analysis to identify key genes associated with carotid-unstable plaque, followed by comprehensive validation using various experimental approaches on tissue specimens and plasma samples classified based on pathological characteristics. Patients with carotid-unstable plaques exhibited elevated plasma concentrations of MD-1 (LY86), while patients with stable plaques demonstrated comparatively lower levels. Furthermore, soluble MD-1 was found to induce the formation of NETs through activation of Toll-like receptor signaling pathway. The proliferative and immature vascularization effects of NETs on endothelial cells, as well as their inhibitory impact on cell migration, are directly correlated with the concentration of NETs. Additionally, NETs were found to activate the NF-κB signaling pathway, thereby upregulating ICAM1, VCAM1, MMP14, VEGFA, and IL6 expression in both Human umbilical vein endothelial cells (HUVECs) and HAECs. Subsequently, a significant increase in intraplaque neovascularization by NETs results in poor carotid plaque stability, and NETs in turn stimulate macrophages to produce more MD-1, generating a harmful positive feedback loop. Our findings suggest that soluble MD-1 in the bloodstream triggers the production of NETs through activation of the Toll-like receptor signaling pathway and further indicate NETs mediate a crosstalk between the microenvironment of the carotid plaque and the neovascularization of the intraplaque region. Inhibiting NETs formation or MD-1 secretion may represent a promising strategy to effectively suppress the development of unstable carotid plaques.